Gestión administrativa y su incidencia en el cumplimiento de obras presupuestadas por el gobierno autónomo descentralizado municipal del Cantón Caluma, Año 2016. - Vengoa Llanos, Maria Fernanda (2016)
A municipality is, an administrative entity of local level; Constituted by a territory, population and public powers. It is an organizational entity within the State that enjoys governmental and administrative autonomy; Whose function is to manage the interests of a community and solve their problems. The Annual Operational Plan (POA) is a short-term action tool whose purpose is to specify and facilitate the effective implementation of the Strategic Institutional Plan (PEI). It contains the elements that allow the allocation of human and material resources to actions that Will make possible the fulfillment of the goals and objectives proposed by the Institution, through the annual programming of the strategic activities defined for each management area; Thus the POA facilitates the monitoring of strategic indicators, directs the institutional management articulates the allocation and the administration of resource in function of objectives and goals. During the period January - December 2016, the Institutional Operative Plan made it possible to guide, consolidate and monitor the objectives, activities, goals and results that the Autonomous Municipal Decentralized Government of Canton Caluma carried out during 2016, in accordance with the budget execution Assigned in the fiscal year, also made it possible to follow up on the goals and contribution of the institution to the National Plan for Good Living, through the fulfillment of the programmed activities and the evaluation of the management and performance of each area. The formulation of the POA 2016 indicators was carried out under the parameters established by the National Secretariat for Planning and Development SENPLADES, based on the operational objectives established in the Development and Territorial Planning Plan in order to support the achievement of the established goals In that plan.